On Misunderstanding the Second Contradiction Thesis - Rudy, Alan P. (Capitalism, Nature, Socialism, 2019)
James O'Connor's "second contradiction" thesis is widely misunderstood as an ecological crisis theory. Most of the criticisms of the theory derive from this misreading, including those which ignore relations between ecological, personal and communal conditions and those which see the "first" and "second" contradictions as materially distinct. O'Connor himself is partially responsible for the misreading, however. His writings tended to put the ecological out front, and his use of Polanyi's romantic idea of "fictitious commodities" reinforced that tendency. The defense developed here rejects ecologistic readings, ties the second contradiction thesis backwards and forwards in O'Connor's work, unpacks the meaning of "conditions" for Marx and O'Connor, and suggests that Neil Smith's argument that capitalist second natural relations generate qualitatively new processes by which nature, human nature and space are produced would have served O'Connor better.
Keywords: MARX, Karl, 1818-1883; O'CONNOR, James; POLANYI, Karl, 1886-1964; SMITH, Neil; conditions of production; contradiction; ecological Marxism; ecologism; environmental marxism; human behavior; second contradiction

Karl Polanyi, the "always-embedded market economy," and the re-writing of The Great Transformation - Lacher, Hannes (Theory & Society, 2019)
This article seeks to subject Fred Block and Margaret Somers' influential reconstruction of Karl Polanyi's The Great Transformation to a systematic review. I show that Block & Somers's central claim—that Polanyi's thinking underwent a "theoretical shift" as he wrote his seminal book—is not supported by archival evidence. I demonstrate that all the narrative keys that Block & Somers advance to lend plausibility to their discovery of a "theory of the always-embedded market economy" in The Great Transformation, wither under critical probing. While this article does not advance a comprehensive alternative reconstruction of Polanyi's main work, the essential continuities it uncovers in his social thought suggest that Polanyi's book is best understood as the culmination of his long-standing efforts to rebuild a radically transformative socialism on non-Marxist foundations. The recognition that Polanyi's political purposes extend far beyond regulated capitalism or social-democracy, I conclude, makes it possible—and indeed necessary—to read The Great Transformation as an internally coherent work of social theory.
Keywords: BLOCK, Fred L.; SOMERS, Margaret R.; capitalism and socialism; critical institutionalism; economic sociology; fascism; neo-Polanyian social theory; political economy

Networked but Commodified: The (Dis)Embeddedness of Digital Labour in the Gig Economy - Wood, Alex J; Graham, Mark; Lehdonvirta, Vili; Hjorth, Isis (Sociology, 2019)
This article investigates the (dis)embeddedness of digital labour within the remote gig economy. We use interview and survey data to highlight how platform workers in Southeast Asia and Sub-Saharan Africa are normatively disembedded from social protections through a process of commodification. Normative disembeddedness leaves workers exposed to the vagaries of the external labour market due to an absence of labour regulations and rights. It also endangers social reproduction by limiting access to healthcare and requiring workers to engage in significant unpaid 'work-for-labour'. However, we show that these workers are also simultaneously embedded within interpersonal networks of trust, which enable the work to be completed despite the low-trust nature of the gig economy. In bringing together the concepts of normative and network embeddedness, we reconnect the two sides of Polanyi's thinking and demonstrate the value of an integrated understanding of Polanyi's approach to embeddedness for understanding contemporary economic transformations.
Keywords: commodification; digital labour; disembeddedness; embeddedness; freelancing; gig economy; outsourcing

Knowledge and social freedom - Rief, Silvia (Journal of Cultural Economy, 2019)
Keywords: Karl Polanyi's Vision of a Socialist Transformation (Book); book review; commentary; freedom

Ethnoracial Populism: An Alternative to Neoliberal Globalization? - Antonio, Robert J. (Social Epistemology, 2019)
Worldwide emergence of strongmen leaderships and eroded or failed democracies suggest that the era of unchallenged neoliberal hegemony may be winding down and that alternatives are rising. The presidential election of Donald Trump has inspired rightwing populists at home and abroad. This paper will analyze the Trumpist fusion of authoritarian ethnoracial nationalism with neoliberal adventure capitalism and the broader matter of how neoliberal de-democratization opens way for right-wing populism and illiberal capitalism. The topics will be explored in part through discussions of earlier theories of Friedrich Hayek, Carl Schmitt, John Dewey, and Karl Polanyi that have been revived and deployed in the current debates over neoliberalism, populism, and democracy.
Keywords: HAYEK, Friedrich A. von (Friedrich August), 1899-1992; POLANYI, Karl, 1886-1964; Presidential elections; SCHMITT, Carl, 1888-1985; Trumpism; de-democratization; ethnoracial populism; globalization; nationalism; neoliberalism; populism; right-wing populism

Karl Polanyi and the Law of Market Society - Frerichs, Sabine (Österreichische Zeitschrift für Soziologie, 2019)
Karl Polanyi started his career as a doctor of law and practiced law for a while; but he did not become a legal scholar. As an economic historian, anthropologist, or sociologist, he was concerned with the relation of economy and society. But even though law is an important factor in mediating this relationship, Polanyi gave little attention to the law as such. As part of an endeavour to advance a ‘Polanyian’ economic sociology of law, this article develops the ‘law of market society’ as an analytical category. For this purpose, three argumentative strategies are combined. First, the article draws on The Great Transformation to reconstruct the role of law in the processes of commodification and decommodification. Second, it turns to Marxist scholarship to explore the conceptual link between law and economics and to ponder to what extent law itself can become a commodity. Third, it links Polanyi’s approach with American institutionalism, and Commons’ work in particular, to show how the evolution of the ‘law of market society’ can also be understood as a collective enterprise which continuously evolves. It is argued that these perspectives complement each other and help to bring the law back in where it is missing.
Keywords: law of market society; sociology of law

Historicizing Karl Polanyi - Gräser, Marcus (Österreichische Zeitschrift für Soziologie, 2019)
Karl Polanyi’s book The Great Transformation has found great resonance in the social sciences in recent years—especially in sociology, political economy and political science. The interest in Polanyi among historians is still modest in comparison. There are not enough studies that treat Polanyi as an object of intellectual history/history of science, nor has Polanyi been used hitherto as an idea-giver for the growing field of global history—despite the fact that his book can be understood as global history. It is high time to “historicize” Polanyi in several ways.
Keywords: history of science; intellectual history

Commodity Studies with Polanyi: Disembedding and Re-Embedding Labour and Land in Contemporary Capitalism - Langthaler, Ernst; Schüßler, Elke (Österreichische Zeitschrift für Soziologie, 2019)
This article aims to inform current debates in the field of transnational commodity studies through a Polanyian lens. Polanyi reminds us of the need to pay attention to the “double movements” in which fictitious commodities are disembedded from and re-embedded in society. We focus on two fictitious commodities, labour and land, which are conventionally treated as mere inputs for the production of genuine commodities. Through investigating the disembedding and re-embedding of labour in the garment industry, and of land in the agro-food sector since the 1970s, we gain insights regarding the commodification of fictitious commodities in the context of transnational commodity chains. The developments in both fields imply not just simple double movements, but complex entanglements of disembedding and re-embedding dynamics at the interface of state, business and civil society actors.
Keywords: commodity studies; double movement

Doing justice to Karl Polanyi - Devine, Pat (Capitalism, Nature, Socialism, 2019)
Keywords: POLANYI, Karl, 1886-1964; book review; economic activity; economics; social control; social forces

Absolute Capitalism - Foster, John Bellamy (Monthly Review: An Independent Socialist Magazine, 2019)
The article deals with the emergence of absolute capitalism due to the efforts of states to promote social reproduction. It explores the association between absolute capitalism and neoliberalism, a ruling-class political-ideological project that is connected to the rise of monopoly-finance capital. Some 20th century thinkers had their own ideas about absolute capitalism, including Karl Polanyi and John Maynard Keynes.
Keywords: KEYNES, John Maynard, 1883-1946; POLANYI, Karl, 1886-1964; capitalism; finance capitalism; neoliberalism; social reproduction

The future of capitalism: Trends, scenarios and prospects for the future - Delanty, Gerard (Journal of Classical Sociology, 2019)
The article provides a framework for thinking about how the question of the future of capitalism might be addressed. One of the problems resides in the very definition of capitalism and of what its defining features consist of and whether we should be talking about 'capitalist society' or the 'capitalist economy' or some kind of post-capitalist condition. Following Polanyi, Castoriadis and Habermas, it is argued that capitalism and democracy together constitute the defining dynamics of modernity and that the resulting tensions will provide momentum for the main circuits of potential change. Five scenarios for looking at the future are discussed. These will form the main substance of the article: varieties of capitalism, systemic crises of capitalism, catastrophic collapse, low growth capitalism and post-capitalism. In conclusion, it is argued that there are various possibilities that can be understood in terms of transitions, breakdown or transformation, but a likely future trend will be less the end of capitalism than the harnessing of 'super-capitalism' and that there are limits to the accumulation of capital.
Keywords: MARX, Karl, 1818-1883; POLANYI, Karl, 1886-1964; SCHUMPETER, Joseph Alois, 1883-1950; WEBER, Max, 1864-1920; capital; capitalism; democracy; future of capitalism; modernity; neoliberalism; varieties of capitalism

Climate Change and the Polanyian Counter-movement: Carbon Markets or Degrowth? - Stuart, Diana; Gunderson, Ryan; Petersen, Brian (New Political Economy, 2019)
In the midst of a wave of market expansion, carbon markets have been proposed as the best way to address global climate change. While some argue that carbon markets represent a modern example of a Polanyian counter-movement to the environmental crisis, we adopt a structural interpretation of Polanyi to refute this claim. Carbon markets represent a further expansion of markets that fails to address the underlying contradictions related to the commodification of nature. In addition, they increase risks to society and the domination of economic elites. While carbon markets further subject social and ecological relations to market mechanisms, we examine degrowth as a possible response to climate change that prioritises social and environmental goals over economic growth. While degrowth continues to be dismissed as impractical or impossible, a growing number of scholars, scientists and activists argue it is the only way to address global climate change. In contrast to carbon markets, we argue degrowth could represent a genuine Polanyian counter-movement in response to climate change. In addition, degrowth could help all those disenfranchised by market fundamentalism by addressing the triple crises related to the commodification of land, labour and money.
Keywords: carbon markets; carbon offsetting; climate; climate change; degrowth; economic development; economic elites; emissions (air pollution); environment; environmental studies

Capitalism in Transformation: Movements and Countermovements in the 21st Century - Atzmüller, Roland; Aulenbacher, Brigitte; Brand, Ulrich; Décieux, Fabienne; Fischer, Karin; Sauer, Birgit (Edward Elgar Publishing, 2019)
Presenting a profound and far-reaching analysis of economic, ecological, social, cultural and political developments of contemporary capitalism, this book draws on the work of Karl Polanyi, and re-reads it for our times. The renowned authors offer key insights to current changes in the relations between the economy, politics and society, and their ecological and social effects.
Keywords: biography; capitalism; countermovement; fictitious commodities

Karl Polanyi and the Global Network Inspired by His Work - Mendell, Marguerite; Aulenbacher, Brigitte; Novy, Andreas (Österreichische Zeitschrift für Soziologie, 2019)